2021
DOI: 10.1016/s1470-2045(21)00453-8
|View full text |Cite|
|
Sign up to set email alerts
|

Vaccine efficacy against persistent human papillomavirus (HPV) 16/18 infection at 10 years after one, two, and three doses of quadrivalent HPV vaccine in girls in India: a multicentre, prospective, cohort study

Abstract: Background A randomised trial designed to compare three and two doses of quadrivalent human papillomavirus (HPV) vaccine in adolescent girls in India was converted to a cohort study after suspension of HPV vaccination in trials by the Indian Government. In this Article, the revised aim of the cohort study was to compare vaccine efficacy of single dose to that of three and two doses in protecting against persistent HPV 16 and 18 infection at 10 years post vaccination. MethodsIn the randomised trial, unmarried g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
88
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(135 citation statements)
references
References 24 publications
1
88
1
2
Order By: Relevance
“…The most recent published study conducted in India showed that the vaccine efficacy against HPV 016 and 18 persistent infection was 95.4% (95% CI = 85.0% to 99.9%) in a single-dose cohort (Table 5) [5].…”
Section: The Real-world Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…The most recent published study conducted in India showed that the vaccine efficacy against HPV 016 and 18 persistent infection was 95.4% (95% CI = 85.0% to 99.9%) in a single-dose cohort (Table 5) [5].…”
Section: The Real-world Effectivenessmentioning
confidence: 99%
“…The 5-year survival rate for all people with cervical cancer is 66.3% [4]. Vaccines against HPV were introduced on the recommendation of the World Health Organization (WHO) and have been available since 2009, 2014, 2017, and 2019 [5]. The recommendations include that the primary target population for HPV vaccination should continue to be girls aged 9-14 years, prior to their becoming sexually active, to be administered two doses, and girls ≥ 15 years of age, including those younger than 15 years known to be immunocompromised and/or HIV-infected (regardless of whether they are receiving antiretroviral therapy), to be administered three doses.…”
Section: Introductionmentioning
confidence: 99%
“…11 For many LMICs, even a two-dose schedule remains beyond reach, a problem compounded by a global shortage of HPV vaccine 20 and, more recently, the COVID-19 pandemic. 21 There is growing evidence from retrospective analyses of incompletely dosed subgroups in randomised controlled trials [22][23][24] and programmes, 25 26 suggesting that a single dose is likely to generate satisfactory immune responses and, hence, protection against new HPV infections, and ultimately cervical cancer. These observations foreshadow potentially huge implementation advantages for cost-savings and coverage, particularly for LMIC settings, 27 and have informed recent suggestions by WHO for countries (in the context of supply and implementation constraints) to consider flexibility in the timing of the second dose for up to 3-5 years after the first dose.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…In this context, recent research results look very promising, i.e. a single dose of vaccination against HPV has a similar efficacy to two and three doses [4]. These results may have far-reaching implications -primarily in a public health context, as it may enable a much faster eradication of HPV regionally and worldwide, moreover, those reluctant to get the HPV vaccine will be more likely to take just one dose, rather than three.…”
mentioning
confidence: 99%